Impact of Digital Transformation on Accounting Information Systems – Evidence from Algerian Firms - Meraghni Oualid; Bekkouche Latifa; Demdoum Zakaria (Economics and Business)
The study aims to demonstrate the conceptual and practical framework of digital transformation and its impact on accounting information systems by focusing on the requirements of digital transformation, such as the digital strategy, the necessary knowledge of the human element, and the effects and obstacles facing the digitization of accounting information systems. The study attempts to answer the following question: What is the impact of digital transformation on accounting information systems in business organisations? The study uses deductive reasoning, based on many previous studies, by applying it to a sample of 237 individuals active in about 120 firms operating in the Algerian environment through a questionnaire distributed in 2021. The study has found a weak degree of awareness of the importance of digital transformation, and a low effort to develop accounting information systems in line with the requirements of digital transformation, all due to the presence of several high-impact challenges.